Effects of TM6SF2 rs58542926 polymorphism on hepatocellular lipids and insulin resistance in early type 2 diabetes - Bódis, Kálmán Benedikt; Bombrich, Maria; Schön, Martin; Knebel, Birgit; Zaharia, Oana-Patricia; Bönhof, Gidon; Karusheva, Yanislava; Strassburger, Klaus; Kupriyanova, Yuliya; Kotzka, Jörg; Guthoff, Rainer; Schrauwen-Hinderling, Vera; et al. (Nutrition, metabolism and cardiovascular diseases, 2023)
Background and aims - Increased hepatocellular lipid content (HCL) is linked to insulin resistance, risk of type 2 diabetes and related complications. Conversely, a single-nucleotide polymorphism (TM6SF2EK; rs58542926) in the transmembrane 6 superfamily member 2-gene has been associated with nonalcoholic fatty liver disease (NAFLD), but lower cardiovascular risk. This case-control study tested the role of this polymorphism for tissue-specific insulin sensitivity during early course of diabetes. - Methods and results - Males with recent-onset type 2 diabetes with (TM6SF2EK: n = 16) or without (TM6SF2EE: n = 16) the heterozygous TM6SF2-polymorphism of similar age and body mass index, underwent Botnia-clamps with [6,6-2H2]glucose to measure whole-body-, hepatic- and adipose tissue-insulin sensitivity. HCL was assessed with 1H-magnetic-resonance-spectroscopy. A subset of both groups (n = 24) was re-evaluated after 5 years. Despite doubled HCL, TM6SF2EK had similar hepatic- and adipose tissue-insulin sensitivity and 27% higher whole-body-insulin sensitivity than TM6SF2EE. After 5 years, whole-body-insulin sensitivity, HCL were similar between groups, while adipose tissue-insulin sensitivity decreased by 87% and 55% within both groups and circulating triacylglycerol increased in TM6SF2EE only. - Conclusions - The TM6SF2-polymorphism rs58542926 dissociates HCL from insulin resistance in recent-onset type 2 diabetes, which is attenuated by disease duration. This suggests that diabetes-related metabolic alterations dominate over effects of the TM6SF2-polymorphism during early course of diabetes and NAFLD.
Online verfügbar 9 June 2023, Version des Artikels 11 August 2023
Gesehen am 06.12.2023